1988
DOI: 10.1111/j.1365-2389.1988.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of phosphate into aggregated particles of ferrihydrite

Abstract: The slow reaction of phosphate with aggregated particles of ferrihydrite, after initial rapid phosphate sorption, was investigated by measuring the changes, with time and temperature, in the amount of phosphate sorbed, and the extractability of the sorbed phosphate. The ferrihydrite was, subsequently, recovered and examined by infra-red spectrometry (IR) and electron probe micro-analysis.Phosphate continued to react with ferrihydrite for at least 90d at 2 5 T , but was completely recovered by extraction with 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 14 publications
(11 reference statements)
6
93
0
Order By: Relevance
“…This is consistent with the results of Gruenhagen et al (1996), who, based on infrared spectra, concluded that coprecipitated P was bonded to ferrihydrite in a manner similar to adsorbed phosphate. Occlusion of P in micropores is not observed when phosphate is reacted with ferrihydrite prepared from pure Fe(III) solutions (Willett et al, 1988).…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with the results of Gruenhagen et al (1996), who, based on infrared spectra, concluded that coprecipitated P was bonded to ferrihydrite in a manner similar to adsorbed phosphate. Occlusion of P in micropores is not observed when phosphate is reacted with ferrihydrite prepared from pure Fe(III) solutions (Willett et al, 1988).…”
Section: Discussionmentioning
confidence: 96%
“…By comparison, an E M P A of phosphate adsorption on ferrihydrite indicated that slow adsorption (after an initially rapid reaction) was the result of the time required for the phosphate to gain access to surface sorption sites located within aggregates of ferrihydrite particles (Willett et al 1988). The authors proposed time-dependent phosphate adsorption as a result of diffusion within aggregates rather than solid-state diffusion.…”
Section: Metal Solubility and Distribution During Ferrihydrite Phase mentioning
confidence: 99%
“…The rapid approach to equilibrium was related to the well crystallized goethite used. For phosphate adsorption on well crystallized goethite, Strauss et al (1997a, b) and Willet et al (1988) found that an adsorption equilibrium was obtained within 1-3 d. The attainment of adsorption equilibrium indicates that the porosity of the goethite is negligible, and that only surface sites are involved in the adsorption process. The only exception was with phosphate in 0.01 M CaC12 electrolyte solutions, where adsorption was initially rapid followed by a slow precipitation reaction.…”
Section: Adsorption/desorption Processesmentioning
confidence: 99%